Identification of Genes With Enriched Expression in Early Developing Mouse Cone Photoreceptors - Buenaventura, Diego F. (Invest Ophthalmol Vis Sci, 2019)
PURPOSE: The early transcriptional events that occur in newly generated cone photoreceptors are not well described. Knowledge of these events is critical to provide benchmarks for in vitro–derived cone photoreceptors and to understand the process of cone and rod photoreceptor diversification. We sought to identify genes with differential gene expression in embryonic mouse cone photoreceptors. METHODS: The specificity of expression of the LHX4 transcription factor in developing cone photoreceptors was examined using immunofluorescence visualization in both mouse and chicken retinas. A LHX4 transgenic reporter line with high specificity for developing mouse cone photoreceptors was identified and used to purify early-stage cone photoreceptors for profiling by single-cell RNA sequencing. Comparisons were made to previous datasets targeting photoreceptors. RESULTS: The LHX4 transcription factor and a transgenic reporter were determined to be highly specific to early developing cone photoreceptors in the mouse. Single-cell transcriptional profiling identified new genes with enriched expression in cone photoreceptors relative to concurrent cell populations. Comparison to previous profiling datasets allowed for further characterization of these genes across developmental time, species, photoreceptor type, and gene regulatory network. CONCLUSIONS: The LHX4 gene is highly enriched in developing cone photoreceptors as are several new genes identified through transcriptional profiling, some of which are expressed in subclusters of cones. Many of these cone-enriched genes do not show obvious de-repression in profiling of retinas mutant for the rod-specific transcription factor NRL, highlighting differences between endogenous cones and those induced in NRL mutants.